Why do Breadwinners Leave Home? - Barsukova Svetlana (Journal of Economic Sociology, 2015)
The presented book review is devoted to “Otkhodniks” by Plusnin Ju., Zausaeva Ya., Zhidkevich N., Pozanenko A. (editor — S. Kordonsky). Otkhodnichestvo is a type of labor migration implying a scenario in which an adult, able-bodied family member temporarily leaves home to seek work in another area. Otkhodnichestvo has a long history in Russia but a new wave of its mass dissemination appeared in recent decades. The reviewed book defines a concept of otkhodnichestvo, considers what similarities and dissimilarities there are between this phenomenon and other forms of labor migration (i.e. jobbers, rotation workers, and temporary cross-border migrants). It reveals the otkhodniks’ motivation and economic patterns, describes typical social and demographic characteristics of contemporary wandering workers, evaluates otkhodniks’ cultural and social impact on local their community’s everyday life, etc. The book is based on a series of fieldwork studies conducted by the authors in small Russian towns over the last four years. The book is published with support from the Social Research Support Foundation “Khamovniki”. In the review Barsukova discusses her impressions of the book, outlining its unusual genre. One uncontestable advantage of the book is an ethnographic material allowing readers to become immersed in all details of otkhodnik life. Otkhodniks usually come from small rural towns. They are forced to leave their homes to seek jobs in other areas because there are no opportunities for them to earn money in their permanent place of residence. Moreover, a key driver of the discussed form of labor migration is the otkhodniks’ aspiration to provide normal living conditions for their family members. The book review author highlights that otkhdoniks should be discussed not just in terms of their informal employment, the context of family relationship transformation should also be taken seriously into account.